Preparation of ZSM-5/MCM-41 composite using naturally occurring diatomite. (18th September 2016) - Yu, Z.; Zhang, Y.; Zhai, S.; Wang, Y.; Liu, X.; Meng, C.
Abstract : ZSM-5/MCM-41 composites with tailored properties have been receiving great attention nowadays; however, their low-cost preparation process remains a challenge. The present study offered a low-cost synthesis of ZSM-5/MCM-41 composite using diatomite as silica source by monitoring the re-crystallisation time in a two-step crystallisation process. The obtained samples were characterised by X-ray powder diffraction, Fourier transform infrared spectroscopy, nitrogen adsorption–desorption measurements, scanning electron microscopy and transmission electron microscopy. It was shown that the resulting ZSM-5/MCM-41 composite possessed a well-ordered mesoporous MCM-41 phase and ZSM-5 microporous phase. The composite was also compared with the mechanical mixture of ZSM-5 and MCM-41 and the results showed that the structure of both materials was different. In addition, the effect of re-crystallisation time on the synthesis of ZSM-5/MCM-41 composite was also investigated in detail. The experimental results indicated that the re-crystallisation time was a key factor for the formation of the composite.